Mediasi Sales Growth pada Transfer Pricing dan Struktur Kepemilikan Terhadap Tax Avoidance - Mahardianik, Ika; Niam, M. Alfa; Isnaniati, Siti (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2023)
Tax avoidance practices are employed by companies to reduce tax burdens. Despite the potential tax reduction, these practices carry the risk of impacting the company's reputation. This research aims to investigate the influence of transfer pricing, institutional ownership, and foreign ownership on tax avoidance, with sales growth serving as an intervening variable. This study adopts a quantitative approach, utilizing secondary data obtained from financial reports of companies for the period from 2020 to 2022. The sample consists of 30 companies in the food and beverage sector listed on the Indonesia Stock Exchange in 2023. Data collection relies on documentation, and the analysis employs multiple linear regression and path analysis techniques.The findings indicate a significant influence of foreign ownership on sales growth, while transfer pricing and institutional ownership do not significantly affect sales growth. Transfer pricing and institutional ownership have a significant impact on tax avoidance, whereas foreign ownership does not influence tax avoidance. The mediating effect reveals that sales growth does not mediate the influence of transfer pricing, institutional ownership, and foreign ownership on tax avoidance.